Combined albumin and bicarbonate induces head-to-head sperm agglutination which physically prevents equine sperm–oviduct binding. Issue 4 (April 2016) - Leemans, Bart; Gadella, Bart M; Stout, Tom A E; Sostaric, Edita; Schauwer, Catharina De; Nelis, Hilde; Hoogewijs, Maarten; Van Soom, Ann
Abstract : In many species, sperm binding to oviduct epithelium is believed to be an essential step in generating a highly fertile capacitated sperm population primed for fertilization. In several mammalian species, this interaction is based on carbohydrate-lectin recognition.d -galactose has previously been characterized as a key molecule that facilitates sperm–oviduct binding in the horse. We used oviduct explant and oviduct apical plasma membrane (APM) assays to investigate the effects of various carbohydrates; glycosaminoglycans; lectins; S-S reductants; and the capacitating factors albumin, Ca 2+ and HCO3 − on sperm–oviduct binding in the horse. Carbohydrate-specific lectin staining indicated that N -acetylgalactosamine, N -acetylneuraminic acid (sialic acid) andd -mannose ord -glucose were the most abundant carbohydrates on equine oviduct epithelia, whereasd -galactose moieties were not detected. However, in a competitive binding assay, sperm–oviduct binding density was not influenced by any tested carbohydrates, glycosaminoglycans, lectins ord -penicillamine, nor did the glycosaminoglycans induce sperm tail-associated protein tyrosine phosphorylation. Furthermore, N -glycosidase F (PNGase) pretreatment of oviduct explants and APM did not alter sperm–oviduct binding density. By contrast, a combination of the sperm-capacitating factors albumin and HCO3 − severely reduced (>10-fold) equine sperm–oviduct binding density by inducing rapid head-to-head agglutination, both of which events were independent of Ca 2+ and an elevated pH (7.9). Conversely, neither albumin and HCO3 − nor any other capacitating factor could induce release of oviduct-bound sperm. In conclusion, a combination of albumin and HCO3 − markedly induced sperm head-to-head agglutination which physically prevented stallion sperm to bind to oviduct epithelium.